2018
DOI: 10.1371/journal.pone.0198461
|View full text |Cite
|
Sign up to set email alerts
|

Circulating proteomic patterns in AF related left atrial remodeling indicate involvement of coagulation and complement cascade

Abstract: BackgroundLeft atrial (LA) electro-anatomical remodeling and diameter increase in atrial fibrillation (AF) indicates disease progression and is associated with poor therapeutic success. Furthermore, AF leads to a hypercoagulable state, which in turn promotes the development of a substrate for AF and disease progression in the experimental setting. The aim of this study was to identify pathways associated with LA remodeling in AF patients using untargeted proteomics approach.MethodsPeripheral blood samples of 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Although, in our studies, we have not addressed the dysregulation of coagulation and the complement system in relation to its contribution to the pathogenesis of AF, several previous reports have provided supportive data on the dysregulation of these processes which lead to tissue damage and a hypercoagulable state. 32 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, in our studies, we have not addressed the dysregulation of coagulation and the complement system in relation to its contribution to the pathogenesis of AF, several previous reports have provided supportive data on the dysregulation of these processes which lead to tissue damage and a hypercoagulable state. 32 36 …”
Section: Discussionmentioning
confidence: 99%
“…Although, in our studies, we have not addressed the dysregulation of coagulation and the complement system in relation to its contribution to the pathogenesis of AF, several previous reports have provided supportive data on the dysregulation of these processes which lead to tissue damage and a hypercoagulable state. [32][33][34][35][36] Besides the electrophysiologic evaluation, imaging techniques such as MRI have become very useful in understanding the structural pathophysiology of AF. 37,38 The data on the collagen remodeling proteins and inflammatory biomarkers reported herein may have a complimentary role to the structural remodeling data obtained with imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…A recent genetic study showed that genetic variation of interleukin-18 is related to a lower risk of atrial fibrillation among people in the Northeast China ( Wang et al, 2017 ). In addition, Kornej et al (2018) reported that complement and coagulation cascades were also related to AF. These reports, together with our findings, further prove the key role of these signals in AF.…”
Section: Discussionmentioning
confidence: 99%
“…[30] The major biological functions of these systems include defense against infections, connecting the innate and adaptive immunity, and the clearance of immune complexes and apoptotic cells. [31] The complement cascade, when activated by the classical, mannose-binding lectin, or alternative pathways, deposits several split products on the cell membrane, ultimately creating a cytotoxic cell lysis complex. [32] The complement split products also include free circulating anaphylatoxins such as C3a and C5a, which can initiate inflammation and tissue injury.…”
Section: Discussionmentioning
confidence: 99%